Iron‐chelating therapy with deferasirox in transfusion‐dependent, higher risk myelodysplastic syndromes: a retrospective, multicentre study. (17th April 2017) - Musto, Pellegrino; Maurillo, Luca; Simeon, Vittorio; Poloni, Antonella; Finelli, Carlo; Balleari, Enrico; Ricco, Alessandra; Rivellini, Flavia; Cortelezzi, Agostino; Tarantini, Giuseppe; Villani, Oreste; Mansueto, Giovanna; et al.
Summary: Iron chelation is controversial in higher risk myelodysplastic syndromes (HR‐MDS), outside the allogeneic transplant setting. We conducted a retrospective, multicentre study in 51 patients with transfusion‐dependent, intermediate‐to‐very high risk MDS, according to the revised international prognostic scoring system, treated with the oral iron chelating agent deferasirox (DFX). Thirty‐six patients (71%) received azacitidine concomitantly. DFX was given at a median dose of 1000 mg/day (range 375–2500 mg) for a median of 11 months (range 0·4–75). Eight patients (16%) showed grade 2–3 toxicities (renal or gastrointestinal), 4 of whom (8%) required drug interruption. Median ferritin levels decreased from 1709 μg/l at baseline to 1100 μg/l after 12 months of treatment ( P = 0·02). Seventeen patients showed abnormal transaminase levels at baseline, which improved or normalized under DFX treatment in eight cases. One patient showed a remarkable haematological improvement. At a median follow up of 35·3 months, median overall survival was 37·5 months. The results of this first survey of DFX in HR‐MDS are comparable, in terms of safety and efficacy, with those observed in lower‐risk MDS. Though larger, prospective studies are required to demonstrate real clinical benefits, our data suggest that DFX is feasible and might be considered in a selected cohort of HR‐MDS patients.